Critical thinking in electricity and magnetism: assessing and stimulating secondary school students. Issue 16 (2nd November 2021) - Sermeus, Jan; De Cock, M.; Elen, J.
ABSTRACT: Critical thinking is one of the most desirable outcomes of education, yet it is often not well defined in curricula. Additionally, there are open questions concerning the domain specificity of critical thinking. In this work, we present two studies aimed at secondary education. Starting from Halpern's conceptualisation of critical thinking we developed a test for assessing critical thinking within the domain of physics (more specifically electricity and magnetism). In the second study, we conducted an intervention study in a quasi-experimental design. Together with experienced teachers, we designed lessons that elicit critical thinking based on the First Principles of Instruction of Merrill. Compared with a control group, the experimental group obtained a significantly higher score on the domain specific critical thinking (measured using the test of the first study), but there was no difference between the groups with regard to domain general critical thinking.